1994
DOI: 10.1002/pd.1970140305
|View full text |Cite
|
Sign up to set email alerts
|

A fetus with a parvovirus B19 infection and congenital anomalies

Abstract: A fetus with multiple structural defects was seen at prenatal ultrasound examination. After termination of the pregnancy a bilateral cleft lip, alveolus, and palate; micrognathia; and webbed joints were seen. Fetal tissues showed indications of infection, intranuclear inclusion bodies, chronic stress, haemolysis, arterial wall damage, and profuse haemorrhage. Parvovirus B19 DNA was detected in fetal tissues by dot hybridization after polymerase chain reaction. The possibility of parvovirus B19 infection leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 8 publications
0
27
0
3
Order By: Relevance
“…Two possible initiators are exogenous factors or genetically encoded morphological errors. Exogeneous causes of facial anomalies include (1) factors causing environmental stress early in embryological development, such as hyperthermia and hypoxia 9 , nutritional deficiencies and hormonal imbalances 16 , (2) viral and toxoplasma infections 5,13 and (3) toxins, drugs and chemicals 15 . In the present case, the role of infectious agents, parasites and drugs could not be obtained because there were no records and history of husbandry of the dam and sire.…”
Section: Discussionmentioning
confidence: 99%
“…Two possible initiators are exogenous factors or genetically encoded morphological errors. Exogeneous causes of facial anomalies include (1) factors causing environmental stress early in embryological development, such as hyperthermia and hypoxia 9 , nutritional deficiencies and hormonal imbalances 16 , (2) viral and toxoplasma infections 5,13 and (3) toxins, drugs and chemicals 15 . In the present case, the role of infectious agents, parasites and drugs could not be obtained because there were no records and history of husbandry of the dam and sire.…”
Section: Discussionmentioning
confidence: 99%
“…It has since been found that fetal B19 infection may also cause fetal or congenital anemia, abortion, or stillbirth or result in an asymptomatic self-limiting episode. A few case reports have speculated on B19 causing congenital malformations (158,335; Weiland et al, Letter, Lancet i:682-683, 1987), though systematic studies have failed to substantiate this hypothesis (47,117,261).…”
Section: B19 Infection In Pregnancy (I) Hydrops Fetalismentioning
confidence: 99%
“…Hepatic disease has also been related to intrauterine infection by parvovirus [10,11]. Furthermore, a fetus with a bilateral cleft lip, alveolus as well as palate, micrognathia and webbed joints after proven fetal B19 infection was reported [12].…”
Section: Discussionmentioning
confidence: 99%